PENERAPAN ZERO WASTE DI RS. WAVA HUSADA DALAM PENGOLAHAN LIMBAH PADAT MENJADI PUPUK - Lukman Arief; Chairumin Alfin; Ahmad Zuhdi; Heru Setiyo (LPPM Universitas Islam Darul 'Ulum Lamongan, 2026)
The increase in healthcare service capacity is directly proportional to the surge in waste generation. The non-medical organic solid waste fraction often dominates and triggers environmental sanitation problems if not managed comprehensively. This Community Service (PkM) aims to implement the Zero Waste concept at Wava Husada Hospital through socio-technical interventions by processing organic solid waste into compost and Liquid Organic Fertilizer (POC). The core problem presented is the high volume of food scraps from the nutrition installation and garden leaf waste following the expansion of the hospital's capacity to 249 beds. The accumulation of this material has the potential to become an attractant for nosocomial disease vectors and incur financial burdens from final disposal retributions. The problem-solving method was formulated using a participatory approach through intensive training and the application of Takakura basket composter technology and anaerobic reactors, collaborating with cleaning staff and representatives of the surrounding community. Scientific findings from this activity showed a significant increase in participants' cognitive understanding by 65% in technical mastery. Furthermore, laboratory testing proved that the quality of the compost produced met the Indonesian National Standard (SNI) 19-7030-2004, marked by a C/N ratio of 15 and optimal macronutrient levels. In conclusion, the decentralized processing of organic waste has proven effective in transforming a cost center into a source of circular economy value-added. The results of this community service play a crucial role as a blueprint for sustainable clinical environmental governance.